The influence of the design parameters on the profile sliding in an internal hypocycloid gear pair - Thai, Nguyen Hong; Giang, Truong Cong (Vietnam Journal of Science and Technology, 2018)
Relative sliding between two profiles in the contact point causes wearing out of the tooth profile. Aiming to evaluate influence of the geometrical dimension parameters of the pump rotor profile on the wear, in this paper, the authors established equation for determining slip coefficient from geometrical dimensions. Furthermore, the authors have investigated and evaluated the phenomenon of the profile slipping in order to find out the geometrical dimensional parameters for avoiding unequal wearing of the inner and outer rotors of the hypogerotor pump